Livelihood Vulnerability Analysis to Climate Variability and Change Risks of Livestock Farming in Karnataka (Indian Journal of Extension Education, 2021)
Vulnerability is reflected in the condition of an economic system as well as socioeconomic characteristics of the population in the system. Assessment of vulnerability can be done using a variety of socioeconomic indicators that capture exposure of the population concerned. Many factors contribute to social and economic vulnerability including rapid population growth, poverty and hunger, poor health, lower education level, gender inequality, social exclusion, marginal and hazardous location, resource degradation, and lack of access to infrastructure, resources and services, including knowledge and technological resources. Exposed population has a limited capacity to protect themselves from natural hazards and bear the brunt of the consequences of large-scale environmental change, including land degradation, biodiversity loss, and climate change, which affect the welfare of the most vulnerable populations. Over the long periods, vulnerable populations have to learn to cope with the effects of climate change on their production systems. Assessing Livelihood vulnerability of a population due to changing climate variables and events and its impact on social and economic eco system is of paramount importance. The Livelihood Vulnerability Index (LVI) was developed to estimate climate vulnerability of livestock farming in Karnataka, India. Two hundred and forty households were surveyed to collect data on socio demographics, livelihoods, social networks, health, food and water security, natural disasters and climate variability. Data were aggregated using a composite index and differential vulnerabilities were compared.